A Novel Role for the BMP Antagonist Noggin in Sensitizing Cells to Non-canonical Wnt-5a/Ror2/Disheveled Pathway Activation - Bernatik, Ondrej; Radaszkiewicz, Tomasz; Behal, Martin; Dave, Zankruti; Witte, Florian; Mahl, Annika; Cernohorsky, Nicole H.; Krejci, Pavel; Stricker, Sigmar; Bryja, Vitezslav (Frontiers in Cell and Developmental Biology, 2017)
Mammalian limb development is driven by the integrative input from several signalling pathways; a failure to receive or a misinterpretation of these signals results in skeletal defects. The brachydactylies, a group of overlapping inherited human hand malformation syndromes, are mainly caused by mutations in BMP signalling pathway components. Two closely related forms, Brachydactyly type B2 (BDB2) and BDB1 are caused by mutations in the BMP antagonist Noggin (NOG) and the atypical receptor tyrosine kinase ROR2 that acts as a receptor in the non-canonical Wnt pathway. Genetic analysis of Nog and Ror2 functional interaction via crossing Noggin and Ror2 mutant mice revealed a widening of skeletal elements in compound but not in any of the single mutants, thus indicating genetic interaction. Since ROR2 is a non-canonical Wnt co-receptor specific for Wnt-5a we speculated that this phenotype might be a result of deregulated Wnt-5a signalling activation, which is known to be essential for limb skeletal elements growth and patterning. We show that Noggin potentiates activation of the Wnt-5a-Ror2-Dishevelled (Dvl) pathway in mouse embryonic fibroblast (MEF) cells in a Ror2-dependent fashion. Rat chondrosarcoma chondrocytes (RCS), however, are not able to respond to Noggin in this fashion unless growth arrest is induced by FGF2. In summary, our data demonstrate genetic interaction between Noggin and Ror2 and show that Noggin can sensitize cells to Wnt-5a/Ror2-mediated non-canonical Wnt signalling, a feature that in cartilage may depend on the presence of active FGF signalling. These findings indicate an unappreciated function of Noggin that will help to understand BMP and Wnt/PCP signalling pathway interactions.